Comparison of perceived training load in cross-country skiing coaches and junior athletes - De Martin Topranin, V.; Noordhof, D. A.; Bucher Sandbakk, S.; Solli, G. S. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Planning and monitoring appropriate training loads in young athletes is crucial to ensure a positive sporting development, minimize the risk of injuries, non-functional states, and ultimately drop-out 1. A recent meta-analysis showed a very low certainty of evidence regarding the agreement between coaches` prescribed and athletes` perceived training load 2. No previous studies have investigated the agreement between intended and perceived training load in cross-country (XC) skiing. Therefore, this study aimed to compare perceived training load in XC skiing coaches and athletes.